Architecture and molecular machinery of skeletal myofibers: a systematic review of the structure–function relationships - Zhao, Jing; Du, Xu; Fang, Wei; Zhu, Hongxia; Yue, Binglin (Frontiers in Cell and Developmental Biology, 2025)
The skeletal muscle, one of the largest tissues in mammals, plays a crucial role in maintaining body movement and energy metabolism. Dysfunction or damage to the skeletal muscle can lead to various muscle diseases, such as muscular dystrophy, myasthenia, and others. The myofiber presents the fundamental structural unit of the skeletal muscle, and research on its structure and biological function is of great significance. Here, we review the latest progress in the structural and functional aspects of the myofiber, focusing on myofibril, the sarcoplasmic reticulum, mitochondria, and the cytoskeleton. The basic properties and dynamic interactions of a large number of muscle proteins have been described in detail, including the scaffold construction of core protein components and the fine-tuning of secondary protein components with functional redundancy. This overview provides new insights into skeletal muscle pathophysiology.